Myoepithelial carcinoma (malignant myoepithelioma) of the parotid gland arising in a pleomorphic adenoma. Issue 7 (July 1998) - McCluggage, W G; Primrose, W J; Toner, P G
Abstract : A myoepithelial carcinoma, a rare malignant salivary gland neoplasm, arose in a pleomorphic adenoma of the parotid gland. The initial tumour was a pleomorphic adenoma with epithelial and myoepithelial elements. Subsequently the tumour recurred twice and was characterised by invasion of the mandible. Histological examination of the second recurrence showed a malignant spindle cell neoplasm with an infiltrative growth pattern and a high mitotic rate. There was involvement of local lymph nodes. The immunophenotype was characteristic of myoepithelial differentiation: tumour cells stained positively with anticytokeratin antibodies, S-100 protein, alpha smooth muscle actin, and vimentin. Electron microscopy confirmed myoepithelial differentiation, with small foci of keratinocytic phenotype. Large numbers of tumour cell nuclei were reactive with the anti-p53 antibody, DO-7, in contrast to the two previous resections. Thus malignant transformation of a pleomorphic adenoma may involve myoepithelial as well as epithelial elements. Accumulation of p53 protein, perhaps through mutational events, may have played a role in this malignant transformation.